2008
DOI: 10.1002/clc.20276
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum C‐reactive Protein Elevation and Atrial Fibrillation After First Anterior Myocardial Infarction

Abstract: Background: Elevated inflammatory markers have been found to correlate with higher risk for cardiac events in patients with acute myocardial infarction (AMI). It has been suggested that C-reactive protein (CRP) may be involved in the initiation process of atrial fibrillation (AF). However, the role of CRP levels in the occurence of AF in patients with AMI has not been studied. This study investigated whether CRP is a risk factor for AF in patients with acute anterior MI. Methods: We prospectively evaluated 92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Although several, but not all, prior studies demonstrated independent associations of CRP with AF in several clinical contexts, 22-24 including AMI 25,26 , these prior studies did not take into account the level of NT-proBNP or TnT in their analyses. The independent association with hsCRP in our markers of myocardial stretch and necrosis are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Although several, but not all, prior studies demonstrated independent associations of CRP with AF in several clinical contexts, 22-24 including AMI 25,26 , these prior studies did not take into account the level of NT-proBNP or TnT in their analyses. The independent association with hsCRP in our markers of myocardial stretch and necrosis are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between markers of myocardial injury and AF events was also evaluated in the literature and multivariate models were created to clarify whether primary myocardial damage per se or associated left ventricular dysfunction was an independent predictor of AF occurrence. Results of a multicenter registry of nonselective myocardial infarction patients suggested that the markers of myocardial stretch (brain natriuretic peptide) and inflammation (CRP), but not the amount of myocardial necrosis (troponin), were found to be important determinants of AF in the setting of myocardial infarction [13]. When STEMI patients admitted for PCI were investigated for the drivers of new-onset AF, a temporal association between troponin plasma levels and the development of AF was reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is characterized as a hyper-inflammatory condition involving the release of pro-inflammatory cytokines and interleukins. The induction of sepsis-induced atrial fibrillation (AF) has been attributed to the generation of an anatomical and electrophysiological substrate from severe inflammation [ 4 , 5 ]. Sepsis is a hyper-inflammatory state that leads to depressed myocardial function.…”
Section: Introductionmentioning
confidence: 99%